Computation Thermodynamic Properties of SuperheatedWater* Far from Critical Region - Kadheem Faleh Al-Hamdi , Tawfeeq (Journal of Engineering and Sustainable Development, 2011)
A general equation has been presented in the present work to calculate specific volume, internal energy, enthalpy and entropy of superheated steam. The developed equation appeared in one context in order to confer upon it the status of generalizing form and away it from complexity that accompanies many equations and great number of mathematical terms that appear in those equations, where the number of terms in the equation presented in present work were eleven terms. Present equations showed a good accuracy for 523 experimental data points to evaluate a selected thermodynamic property of superheated steam. The average absolute percentage of error for those properties not exceed 1%, where the average absolute percentage of error 0.687% for specific volume, 0.767% for the internal energy, 0.867% for enthalpy and 0.654% for entropy.